ANALYSIS OF E-VILLAGE BUDGETING SYSTEM EFFECTIVENESS IN VILLAGE FINANCIAL MANAGEMENT IN BANYUWANGI DISTRICT (Case Study in Genteng Wetan Village, Genteng District) - Wahyuni, Endang Dwi; Mubaroq, Guntur Kumar; Latifah, Sri Wahjuni (Universitas Muhammadiyah Malang)
This study aims to describe the application of E-Village Budgeting System at Genteng Wetan Village based on Banyuwangi Regent Regulation No. 15 of 2015 about Village Finance Management. And analyze the effectiveness of E-Village Budgeting System Based on indicators of technology-based information systems. This research method is Descriptive research using qualitative approach. The results of this study show that Village Finance Management using E-Village Budgeting System in Genteng Wetan Village is in accordance with Banyuwangi Regent Regulation No. 15 year 2015. Security aspect is sufficient but there are still some deficiencies such as the autosave data and external disturbances. Aspects of Speed already good can be seen from the fast E-Village Budgeting system in input, process, and analyze data. Aspects of Accuracy are good enough but still needed separator to reduce errors in input data. Variation Aspects Report (output) and Relevance is sufficient can be seen from the results or outputs are produced in accordance with applicable accounting standards. The quality of financial reports generated with the help of the E-Village Budgeting system is good. So, in general the application of E-Village Budgeting system is quite good and effective. Â However, there are still some lack of security aspects of the E-Village Budgeting System At Genteng Wetan Village